Library-park with social and cultural integration in the city of Huánuco - Daga Almerco, Bekin Bauer (2025)
The library is an essential cultural space for the preservation and dissemination of heritage, as it promotes civic development and ensures equitable access to information. In Peru, public library infrastructure remains insufficient, with a density as low as 1.62 libraries per 100,000 inhabitants. This scarcity limits both social and cultural progress, particularly in vulnerable and underdeveloped areas. In the case of Huánuco, 83.3% of municipalities lack public libraries, and those that exist operate under precarious conditions. To address this gap, the proposal introduces the design of a library park that integrates social, cultural, and educational functions, fostering citizen interaction and strengthening cultural and social ties. This space is conceived as an open and dynamic environment aimed at reducing socio-cultural disparities, enhancing public safety, and consolidating community bonds.